Evaluation of public bus demand along the Butterworth-Kepala Batas route / Elizebeth Loren anak Ajis - Anak Ajis, Elizebeth Loren (Faculty of Civil Engineering, 2007)
Public transport especially bus are needed in our live to travel from one place to another. Nowadays, the supply of public bus has been questioned whether it can cater the demand of users. This report discussed on the demand of public transportation but limited to public bus along the Butterworth - Kepala Batas route which focused on the operation of bus number 89 provided by United Traction Company (UTC). The objectives are to evaluate the demand and improve the public bus service along this route. Questionnaires survey was conducted to report on the present demand and travel behavior of users. Other than that field observations were done to see the actual condition of public bus demand. The overall finding is that the supply of public bus is sufficient but the service should be improved in the future. This report provides an introduction to the evaluation of public transport demand along the Butterworth - Kepala Batas route and recommendations to provide a better service in the future.